Joint Estimation of Remission and Response for Methotrexate‐Based DMARD Options in Rheumatoid Arthritis: A Bivariate Network Meta‐Analysis. Issue 8 (8th August 2019) - Pokharel, Gyanendra; Deardon, Rob; Barnabe, Cheryl; Bykerk, Vivian; Bartlett, Susan J; Bessette, Louis; Boire, Gilles; Hitchon, Carol A; Keystone, Edward; Pope, Janet; Schieir, Orit; Tin, Diane; et al.
Abstract : Objective: To jointly estimate American College of Rheumatology (ACR50) response (a more commonly reported outcome) and remission (a more clinically relevant outcome) for methotrexate (MTX)‐based treatment options in rheumatoid arthritis (RA). Methods: We conducted a bivariate network meta‐analysis (NMA) to compare MTX monotherapy and MTX‐based conventional and biologic disease‐modifying antirheumatic drug (DMARD) combinations for RA. The correlation between the outcomes was derived from an incident RA cohort study, whereas the treatment effects were derived from randomized trials in the network of evidence. The analyses were conducted separately for MTX‐naïve and MTX–inadequate response (IR) populations in a Bayesian framework with uninformative priors. Results: From the cohort study, the correlation between ACR50 response and Disease Activity Score 28 remission at 6 months was moderate (Pearson correlation coefficient = 0.58). In the bivariate NMA for MTX‐naïve populations, most combinations of MTX with either biologic or tofacitinib were statistically superior to MTX alone for both ACR50 response and remission. Triple therapy (MTX + sulfasalazine + hydroxychloroquine) was the only nonbiologic DMARD statistically superior to MTX for either ACR50 response (odds ratio [OR] 95% credible interval: 2.1 [1.0, 4.3]) or remission (OR: 2.5 [1.0, 5.8]). In the MTX‐IR analysis, all treatments except MTX + sulfasalazine were statistically superior to MTX alone. Compared to analyzing the outcomes separately, the bivariate model often resulted in more precise estimates and allowed remission to be estimated for all treatments. Conclusion: Borrowing the strength of correlation between outcomes allowed us to demonstrate a statistically significant benefit for remission across most MTX‐based DMARD combinations, including triple therapy.